ANALISA PENGARUH INTI KOIL TERHADAP MEDAN MAGNETIK DAN MUATAN PADA KAPASITOR DALAM RANGKAIAN SERI LC - Maksi Ginting, Salomo Erwin, Usman Malik, (Universitas Pasir Pengaraian, 2017)
Magnetic field that produced by coils changes its value significantly when the coil core made from air replaced by ferromagnetic (Fe), paramagnetic (Cu) and diamagnetic (Al) materials. In this research the value of magnetic field was measured as a function of coil’s turns (N), Applied Current (I) and the distance From the center of the coil as the coil’s core changed from air to Fe, Cu, and Al. Number of turns of the coils was varied namely 50, 100, and 150 with length of 4.2 cm and diameter of 3.2 cm. Next, the coil and a capacitor were connected with a series circuit in which the value of the capacitance of the capacitor is 4700 μƒ. Magnetic field that produced by the coils were measured using Pasco Magnetic Probe PS- 2162 . While the voltage were measured using volt meter. From the result of the research it was found that the average value of magnetic field (N = 50 turns) for constant current of (2A) increased by 127 % and 13.59 % when the core coil (air) replaced by iron and copper respectively. While for alumunium, the value of the magnetic field was reduced by 45.56 % from air core. Theoretically, the value of charges on the capacitor and current flow in the circuit as a function of time oscillated in the form of sinusoidal. The charges on the capacitor at t=0 had its maximum value that was 9.4 x 10-4 Coulomb, the current in the circuit reached its maximum value that was 5.08 Ampere at t = 10 s.